Study on bearing capacity of reinforced concrete beams strengthened with carbon fiber reinforced polymer sheet - Jie Li (Lowland Technology International, 2021)
In this study, the strengthening effect of the carbon fiber reinforced polymer (CFRP) sheet was studied. Four groups of specimens were designed, each of which has three specimens. The specimens were strengthened with 0 layer of CFRP sheet, one layer of CFRP sheet, two layers of CFRP sheet, and three layers of CFRP sheet, respectively. An experiment was carried out through the third-point loading method. Compared with the unreinforced reinforced concrete (RC) beams, the load of the beams strengthened with CFRP sheet significantly increased. Taking the ultimate load as an example, compared with the RC beams, the RC beams strengthened with one, two and three layers of CFRP sheet increased by 7%, 19%, and 23%, respectively; under the same load level, the mid-span deflection of the beam reduced, and the anti-deformation ability significantly improved. The experimental results show that the CFRP sheet can improve the bearing capacity of beams and can be further applied in practical engineering.